PENGARUH PENGEMBANGAN KARIR, SELF EFFICACY, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA DINAS KESEHATAN KABUPATEN BANGLI - Ni Putu Arya Juliantari; Gde Bayu Surya Parwita; Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
This study aims to determine the effect of career development, self efficacy, and physical work environment on employee performance. The location of this study is at the Bangli District Health Office. The population used employees at the Bangli District Health Office and a sample of 64 employees determined by saturated sampling techniques. Data analysis techniques use Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, Coefficient of Determination, F Test and t Test. The results showed that career development had a positive and significant effect on employee performance, self efficacy had a positive and significant effect on employee performance, and the physical work environment had a positive and significant effect on employee performance. The advice that can be given by researchers is that the Bangli District Health Office should provide socialization on career development procedures to employees, rearrange the workspace to be more comfortable, and always provide motivation to employees.